STANDARDIZATION OF PACKAGING CONTAINERS FOR STORAGE OF MANGO (MANGIFERA INDICA L.) CANDY - PRAVEEN KUMAR MISHRA; VIKASH KUMAR MISHRA; GULAB SINGH; VINOD SINGH; SANJAY SAHAY; PIYUSH SHRIVASTAVA; V. K. MAURYA (The Bioscan, 2015)
The present research was carried out during the year 2012-13 at the Department of Horticulture, N. D. U. A. & T., Kumarganj, Faizabad (U.P.) India to standardized the packaging container for storage stability of mango (Mangifera indica L.) candy (osmo-dehydrated product). The prepared candy of Mallika variety was stored in different packaging containers like glass jars, plastic jar and LDPE packet at ambient condition. The qualitative attributes of prepared candy were observed at monthly interval up to 10 months of storage period and observed the LDPE packet was superior over other containers because least changes were observed in biochemical constituents, viz. ascorbic acid (6.2 mg/100g), total sugars (71.0 %), β-carotene (1.9 mg/100g), total phenols (14.4 mg/100g) and also prevent from physiological losses in weight by retaining maximum weight (192.0 g) with maintained higher organoleptic score (7.8) at the end of storage period. This experiment will be very helpful for commercialization of mango candy among processors, industrialist as well as consumers in perspective of stability, price and round the year availability.